Energy Poverty and Carbon Emissions: The State of Luzon, Philippines - Neil Stephen A. Lopez; Christian Roice C. Tayag; Ivan Henderson V. Gue (Chemical Engineering Transactions, 2023)
The prevalence of energy poverty on a global scale has been a longstanding concern, particularly in developing countries. In the Philippines, 1.6 million households had no access to electricity in 2020, owing to high power costs at around 0.20 $/kWh, the most expensive in the ASEAN region. While the energy poverty in the Philippines is apparent, energy consumption and carbon emission levels are assessed only on the national level in the past due to limited data. This study assessed the possible relationship between household energy consumption and emission levels with income by using data from the Family Income and Expenditure Survey (FIES) Report, which holds information on a household's income, energy expenses, and other relevant socioeconomic indicators. Additionally, Gini coefficients for energy consumption and carbon emissions are calculated to investigate the distribution of energy use within the population and assess which income group contributes the highest emissions. The Gini coefficient for electricity at 0.40 indicates greater consumption and emission inequity due to income disparity when compared with the 0.20 coefficient for non-electricity carbon emission. This indicates a direct relationship between income and electricity reliance. The non-electricity emission of 1.32 t CO2e per capita in comparison with electricity emission of 0.17 t CO2e per capita shows that poor households contribute higher overall emissions due to the inability to rely on electricity. Findings from this study can be used by policymakers to pursue a targeted approach with consideration of income in creating energy regulations.